Contemporary cybernetic and systemic researches - Rudall, B. H. (Brian H.) (Kybernetes ;, 2002)
This Special Double Issue is designed to publicise the work of researchers inmany of the specific areas of the study of systems and cybernetics. All, however, have a common bond in that they illustrate an interdisciplinaryapproach and communicate important research studies.